LEADER: Results and problems at local level - Blága, Ágnes (Socio.hu Társadalomtudományi Szemle, 2015)
Leo Granberg, Kjell Anderson and Imre Kovách (editors): Evaluating the European Approach to Rural Development: Grass–roots Experiences of the LEADER Programme Ashgate, 2015